A review on neurodevelopmental abnormalities in congenital heart disease: focus on minimizing the deleterious effects on patients. Issue 1 (1st January 2021) - Zheng, Bai-hong; Liu, Xiu-min; Zhao, Peng; Li, Ping
Abstract : Due to the surgical procedures, the longevity of congenital heart patients is dramatically increased; however, these patients suffer from concomitant neurodevelopment abnormalities, which include deficits in cognitive, executive and behavioral functions. There are more chances of seizure development and incidences of ischemic stroke in these children. Indeed, there are pathological changes in the brain, which include a reduction in the volume of the brain, metabolic alterations, alterations in the functional connectivity, dysregulation of angiogenesis and changes in the apparent axon density along with orientation dispersion. The management of neural abnormalities depends on the type of symptoms observed in these patients. There have been limited studies that have focused on identifying the interventions that may limit the impact of neurodevelopmental abnormalities. It has been reported that dexmedetomidine, α2 -adrenergic receptor agonist, produces neuroprotection in infants undergoing surgery for congenital heart disease. Moreover, there have been some studies focusing on the impact of mode of feeding, anticoagulation, and effect of other anesthetics on the neurodevelopmental changes in congenital heart disease pediatrics. The present review discusses the neurodevelopment abnormalities in congenital heart disease pediatrics with a focus on different interventions that have been explored by different scientists to limit the deleterious effects on the patients.